HDL-C and non-HDL-C levels are associated with anthropometric and biochemical parameters - Sandra Maria Barbalho; Ricardo José Tofano; Marcela Bueno de Oliveira; Karina Rodrigues Quesada; Mariana Ricci Barion; Marina Cristina Akuri; Marie Oshiiwa; Marcelo Dib Bechara (Jornal Vascular Brasileiro, 2019)
Abstract Background Dyslipidemias are associated with atherosclerosis and cardiovascular diseases. Recently, non-high-density lipoprotein cholesterol (non-HDL-c) has emerged as a new target for assessment and prediction of risk of cardiovascular disease (CVD) and is closely associated with atheroma plaque progression. Objectives To evaluate associations between HDL-c and non-HDL-c levels and anthropometric and biochemical parameters and with the Castelli risk indexes I and II. Methods 300 randomly selected people were subdivided into two groups: patients with normal values for non-HDL-c and patients with altered values for non-HDL-c. These parameters were analyzed for associations with glycemia, total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL-c), Castelli Index I (CI-I), Castelli Index II (CI-II), waist circumference (WC), body mass index (BMI) and presence of metabolic syndrome (MS). Results Glycemia, TC, TG, LDL-c, CI-I, CI-II, WC and BMI were all significantly different between subjects with normal and altered values of HDL-c and non-HDL-c. TC and WC both exhibited significantly higher values among patients with abnormal non-HDL-c when compared to patients with abnormal HDL-c. A significant difference was observed in occurrence of MS among patients with altered values of HDL-c and non-HDL-c. Conclusions Our results show that both HDL-c and non-HDL-c are associated with insulin resistance, dyslipidemia, atherogenic indices, and obesity. There is therefore a need for randomized clinical intervention trials examining the potential role of non-HDL-c as a possible primary therapeutic target.